2017
DOI: 10.18632/oncotarget.15952
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bond disrupting agents activate the unfolded protein response in EGFR- and HER2-positive breast tumor cells

Abstract: Many breast cancer deaths result from tumors acquiring resistance to available therapies. Thus, new therapeutic agents are needed for targeting drug-resistant breast cancers. Drug-refractory breast cancers include HER2+ tumors that have acquired resistance to HER2-targeted antibodies and kinase inhibitors, and “Triple-Negative” Breast Cancers (TNBCs) that lack the therapeutic targets Estrogen Receptor, Progesterone Receptor, and HER2. A significant fraction of TNBCs overexpress the HER2 family member Epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 71 publications
5
35
0
Order By: Relevance
“…An unexpected and striking finding is the apparent selectivity of DDAs against cancer cells over normal cells in vitro and in vivo (herein (Fig. 6C) and elsewhere (Ferreira et al, 2015, Ferreira et al, 2017). Multiple mechanisms explain the oncotoxicity of DDAs.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…An unexpected and striking finding is the apparent selectivity of DDAs against cancer cells over normal cells in vitro and in vivo (herein (Fig. 6C) and elsewhere (Ferreira et al, 2015, Ferreira et al, 2017). Multiple mechanisms explain the oncotoxicity of DDAs.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies revealed that breast cancer cells that overexpress EGFR or HER2 are particularly sensitive to DDAs (Ferreira et al, 2015, Ferreira et al, 2017, Wang, Ferreira et al, 2019. This work employed MDA-MB-468 TNBC cells and BT474 luminal B cells as models of EGFR and HER2 overexpressing breast cancer, respectively.…”
Section: Ddas Activate Extrinsic Apoptosis Pathway To Kill Egfr+ and mentioning
confidence: 99%
See 3 more Smart Citations